2023
DOI: 10.3390/plants12132471
|View full text |Cite
|
Sign up to set email alerts
|

Developing Functional Relationships between Soil Moisture Content and Corn Early-Season Physiology, Growth, and Development

Abstract: Drought is a severe threat to agriculture production that affects all growth stages of plants, including corn (Zea mays L.). Any factor affecting early seedling growth and development will significantly impact yield. Despite the recurrence of low rainfall during the growing seasons, corn responses to different early-season soil moisture content levels have not been investigated. In this study, we investigated how corn morpho-physiological and biomass traits responded to varied soil moisture content during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“…These results indicate that the stressed maize and sorghum plants invest in their root systems via allocation of more resources to their roots to support the changes in root morphology necessary to maximize water and nutrient uptake under drought stress [14]. Consistent with that, it has been reported that droughted green-house maize and sorghum plants develop deeper roots to absorb enough water and reduce the incidence of water deficits [66,67]. Further, it has been reported that maize hybrids that develop higher root/shoot ratio values can effectively survive drought stress [68].…”
Section: Discussionsupporting
confidence: 69%
“…These results indicate that the stressed maize and sorghum plants invest in their root systems via allocation of more resources to their roots to support the changes in root morphology necessary to maximize water and nutrient uptake under drought stress [14]. Consistent with that, it has been reported that droughted green-house maize and sorghum plants develop deeper roots to absorb enough water and reduce the incidence of water deficits [66,67]. Further, it has been reported that maize hybrids that develop higher root/shoot ratio values can effectively survive drought stress [68].…”
Section: Discussionsupporting
confidence: 69%
“…Plants are known to modify their morphology and their physiological and molecular functions in response to reduced soil moisture but the variation is influenced by the growth stage and by the species. These changes affect most of the biochemical processes of the plants, and in most cases, the effect is negative, such as a reduction in the photosynthetic capacity of the plant [49].…”
Section: Discussionmentioning
confidence: 99%
“…Five levels of soil moisture regimes with 20 replicates for each treatment were created based on the United States Drought Monitor Index (USDM, 2023) to mimic drought conditions during flowering and grain‐filling periods. The soil moisture regimes were maintained by varying levels of VWC, with a control of 0.25 m 3 m −3 , and stress treatments with VWC levels of 0.20 (mild), 0.15 (moderate), 0.10 (severe), and 0.05 (extreme) m 3 m −3 , as described in the previous study (Vennam et al, 2023). Different irrigation durations were employed to accomplish the desired VWC levels, with 1000 ml plant −1 day −1 as the control, and a reduced irrigation of 800, 600, 400, and 200 ml plant −1 day −1 to induce soil moisture stress (Figure 1A, B).…”
Section: Methodsmentioning
confidence: 99%
“…The study was conducted at the R.R. (mild), 0.15 (moderate), 0.10 (severe), and 0.05 (extreme) m 3 m À3 , as described in the previous study (Vennam et al, 2023). Different irrigation durations were employed to accomplish the desired VWC levels, with 1000 ml plant À1 day À1 as the control, and a reduced irrigation of 800, 600, 400, and 200 ml plant À1 day À1 to induce soil moisture stress (Figure 1A, B).…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%